Skenario Pengembangan Wilayah Berbasis Daerah Irigasi (Studi Kasus : di Cihea Kabupaten Cianjur) - Endang Purnama Dewi; M. Yanuar J Purwanto; Asep Sapei (Balai Teknik Irigasi, 2014)
Regional development is targeted to make better growth in the rural area, by improving farmer’s welfare and minimizing the gap among the regions. In particular, the developement aims to increase farmers income percapita as an income indicators of development in rural area. In the irrigation area, the regional development can also increase the domestic revenue by providing value added program in this region. The existing regional plan (RTRW) of Cianjur in 2013 –2031 a part of the study area (Cihea irrigation system) are planned to be converted in to industrial area, it reaches 4209.903 ha. This research aims to provide an irrigation system based development strategy for guiding to the implementation of the RTRW. In the irrigation system, there are water resources and agricultural activities, mostly in food comodities. These resources will be considered in the study in order to achieve the target of rural development as for the implemention of RTRW. In this research, it analyzed supply and demand of irrigation, based on water balance calculation and farm production, the prospective industrial area in the region for processing the raw product of farming. As the result, the agricultural land convertion should be targeted into processing plant for rice. By these scenarios, the water resources were able to irrigate area of 5.484 ha with cropping pattern of rice-rice -secondary foodcrop as the minimum discharge occured in September its about 0.553 m3/second. The total production of this raw agricultural product can be processed to rice snack and cereal beside of rice, thus being able to gave rise in income of farmer to Rp 2.461.706,00 per planting season. Based on spatial analyze, the area which is can be developed are Ciranjang, Sukaratu, Sindangjaya, Mekargalih, Bojongpicung, Kertajaya, dan Cibiuk.